PENGEMBANGAN SUMBER DAYA MASYARAKAT SEKITAR HUTAN YANG PERTISIPATIF MELALUI PELATIHAN KONSERVASI HUTAN LAHAN - Asrul, Muhammad; Wiharto, Muhammad; Pertiwi, Nurlita (Pascasarjana Universitas Negeri Makassar, 2023)
Humans and the environment are a complete ecosystem unit, where one cannot be separated from one another. The unity of the ecosystem includes ecological, economic, socio-cultural aspects, which are intertwined in human civilization. However, a series of human activities are often the cause of various cases of environmental degradation. The aim of the research was to find out the knowledge, attitudes and skills of the community before and after being given training on land forest conservation. The research was conducted in Palopo City, especially Wara Barat District, with a total sample of 20 people selected through purposive sampling. The study used a descriptive quantitative pre-experiment and was analyzed using the Paired Sample T test. The results showed that after being given training on land conservation management, the knowledge, attitudes and skills of the community increased significantly. This indicates that the training has had a positive influence and changed the understanding of land forest conservation.